11 September and Its Aftermath : The Geopolitics of Terror - Edited by Stanley D. Brunn with a Foreworded By David Newman (London Frank Cass, 2004)
The essays that comprise this collection explore the ramifications of the events of 11 September 2001 and global reactions to it.
Include Abstract, Index and Notes.
Keywords: September 11 Terrorist Attacks (2001) -- World Politics -- 21st Century